Silica, silicosis and cancer in Finland - Partanen, Timo; Jaakkola, J.; Tossavainen, Antti (Scandinavian Journal of Work, Environment & Health, 1995)
Approximately 100 000 Finnish workers are currently employed in jobs and tasks that may involve exposure to airborne silica dust. The major industries involved are mining and quarrying; production of glass, ceramics, bricks and other building materials; metal industry, particularly iron and steel founding; and construction. Over 1500 cases of silicosis have occurred in Finland since 1935. Tuberculosis has been a frequent complication of silicosis. Results of studies from several countries strongly suggest that silica dust also causes lung cancer. The results of the relevant Finnish epidemiologic and industrial hygiene studies addressing cancer risk and exposure to quartz dust are summarized.
Keywords: ceramics; construction; dust; excavation; glass; iron founding; lung cancer; mining; steel casting; stone industry